Analisis Implikatur Baliho Bakal Calon Legislatif/DPRD di Kabupaten Serang Tahun 2024 dan Implementasinya dalam Pembelajaran Bahasa Indonesia di SMP - Dalilah Dalilah; Dase Erwin Juansah; Ilmi Solihat (CV. ULIL ALBAB CORP, 2024)
This study aims to find out the implications contained in the Billboards for Prospective Legislative Candidates/DPRD in Serang Regency in 2024 and its implementation in Indonesia language learning in junior high school. This implication analysis research uses a qualitative research method. The data collection technique uses observation techniques, documentation techniques, and note-taking techniques. Meanwhile, the data analysis technique in this study uses data reduction techniques, presentation of data analysis results, and drawing conclusions. The results of the study found: (1) The types of implications contained in billboards for prospective Legislature/DPRD candidates in Serang Regency in 2024 are conventional implications and conversational implications. (2) The function of the implications contained in the billboards of prospective Legislative Candidates/DPRD in Serang Regency in 2024 is that in the conventional implication data, it is found that the types of speech acts of the commissioner promise, directive to invite, directive to ask or beg, assertively inform, and assertively suggest. Meanwhile, in the data on the implication of the conversation, it was found that the types of speech acts were assertive, directive to invite, commission to promise, and assertive to inform. (3) The results of the research are used as an implementation in Indonesian learning in grade VIII (eight) junior high school by creating a teaching module on the material of recognizing messages in commercial advertisements.